Two new species of Podonomus Philippi (Diptera: Chironomidae: Podonominae) from mountains of Southeastern Brazil - Shimabukuro, Erika Mayumi; Pepinelli, Mateus; Trivinho-Strixino, Susana (Zootaxa, 2017)
Two new species of Podonomus from southeastern Brazil are described. The adults and pupa of Podonomus mina sp. nov. and the male adult and the pupa of Podonomus itatiaia sp. nov. were described based on specimens collected from mountaintops. DNA barcodes of Podonomus mina sp. nov. were analyzed to investigate the molecular divergence among Podonomus populations in Brazil, and used as a tool to associate different development stages and sexes. The immature stages of P. mina sp. nov. and P. itatiaia sp. nov. live in madicolous habitats.